2013
DOI: 10.1155/2013/137579
|View full text |Cite
|
Sign up to set email alerts
|

Lipotoxicity: Effects of Dietary Saturated and Transfatty Acids

Abstract: The ingestion of excessive amounts of saturated fatty acids (SFAs) and transfatty acids (TFAs) is considered to be a risk factor for cardiovascular diseases, insulin resistance, dyslipidemia, and obesity. The focus of this paper was to elucidate the influence of dietary SFA and TFA intake on the promotion of lipotoxicity to the liver and cardiovascular, endothelial, and gut microbiota systems, as well as on insulin resistance and endoplasmic reticulum stress. The saturated and transfatty acids favor a proinfla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(129 citation statements)
references
References 106 publications
(135 reference statements)
2
108
0
5
Order By: Relevance
“…Thus, reticulum stress disturbs hepatic lipid metabolism by deregulation of lipogenic genes, promotes insulin resistance, and activates several proinflammatory pathways as NF-B [73,74]. It has been described that the inflammatory response mediates the effect of dysbiosis and endotoxemia in ER stress development [75].…”
Section: Thus Quercetin Reduced the Increased Firmicutes/bacteroidetesmentioning
confidence: 99%
“…Thus, reticulum stress disturbs hepatic lipid metabolism by deregulation of lipogenic genes, promotes insulin resistance, and activates several proinflammatory pathways as NF-B [73,74]. It has been described that the inflammatory response mediates the effect of dysbiosis and endotoxemia in ER stress development [75].…”
Section: Thus Quercetin Reduced the Increased Firmicutes/bacteroidetesmentioning
confidence: 99%
“…It is known that the inflammatory response caused by these mediators induces vascular endothelial dysfunction and macrophage activation 9) , leading to the development and progression of atherosclerosis. In particular, an excess of saturated fatty acids is considered a risk factor for cardiovascular disease and has been reported to trigger inflammatory signals in various tissues and promote lipotoxicity 10) . In order to elucidate the mechanism of the anti-atherogenic effect of EPA, we studied lipotoxicity in vascular cells and showed that palmitic acid (PA), a major saturated fatty acid in plasma, stimulates inflammatory cytokine production in macrophages as well as osteoblastic differentiation of vascular smooth muscle cells, and that this action could be mediated by long-chain acyl-CoA synthetase (ACSL), an enzyme that converts free fatty acids into acyl-CoA derivatives 11,12) .…”
Section: Elisamentioning
confidence: 99%
“…The prolonged exposure to oxidative stress has been implicated in the development or acceleration of several diseases such as cardiovascular disease and autoimmune diseases (Estadella et al 2013).…”
Section: Introductionmentioning
confidence: 99%